If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 3(z + 2) + -11z = -7(z + 2) + 14 Reorder the terms: 17 + 3(2 + z) + -11z = -7(z + 2) + 14 17 + (2 * 3 + z * 3) + -11z = -7(z + 2) + 14 17 + (6 + 3z) + -11z = -7(z + 2) + 14 Combine like terms: 17 + 6 = 23 23 + 3z + -11z = -7(z + 2) + 14 Combine like terms: 3z + -11z = -8z 23 + -8z = -7(z + 2) + 14 Reorder the terms: 23 + -8z = -7(2 + z) + 14 23 + -8z = (2 * -7 + z * -7) + 14 23 + -8z = (-14 + -7z) + 14 Reorder the terms: 23 + -8z = -14 + 14 + -7z Combine like terms: -14 + 14 = 0 23 + -8z = 0 + -7z 23 + -8z = -7z Solving 23 + -8z = -7z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '7z' to each side of the equation. 23 + -8z + 7z = -7z + 7z Combine like terms: -8z + 7z = -1z 23 + -1z = -7z + 7z Combine like terms: -7z + 7z = 0 23 + -1z = 0 Add '-23' to each side of the equation. 23 + -23 + -1z = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -1z = 0 + -23 -1z = 0 + -23 Combine like terms: 0 + -23 = -23 -1z = -23 Divide each side by '-1'. z = 23 Simplifying z = 23
| 20x+53= | | 2p-(1+8p)=4p-21 | | (15-y)+2=2y | | -2x+3=4x+75 | | Y+7-3=12 | | xz^2+z^2-3zx+4z-70x+70=0 | | 200-80=2l+80-80 | | 8r+7=49 | | s=p(1+rt) | | 14+s=-32 | | 4-3n=2n-36 | | -58+58=29p-14p | | 1x+5=3x-1 | | 4(x+5)=6x+4-2x+16 | | 9*0-7=-7 | | 7(m+7)=36-6m | | (x-2)(3+y)=(x-2)(3+y) | | 7m^6+m-3(m^6+4m)= | | .67a-14=61 | | 10x-20= | | 168-80=2l+80-80 | | (2x+3)*(x-2)-x*(x-1)=0 | | 3(2x-2)+7=2(x+5) | | 6(n-5)-lIn=0 | | 4m+7=19-2m | | Y+14=-33 | | -15y+9x=105 | | -12=0.4x-0.7x | | 3x^2-4x+16=0 | | K-9=-4 | | 9x-15y=105 | | -4(4-7x)+7=-9+7x |